Ibn Bajjah's Concept of Al-Mutawwahid as a Form of Stress Management and Mental Health in the Modern Era - Agil Shodiki Manurung; Gazali (Institut Ilmu Al-Qur'an (IIQ) An-Nur Yogyakarta Komplek PP An Nur Ngrukem PO BOX 135 Bantul 55702 Yogyakarta Tlp/Fax (0274) 6469012. http://jurnalannur.ac.id/, 2025)
The phenomenon of increasing stress and mental health disorders in the modern era has become a global challenge that requires a new approach that is not only psychological but also philosophical. In this context, the thinking of Ibn Bajjah through the concept of al-mutawwa??id or solitary man offers an interesting reflective framework. This problem formulation includes: (1) How is the concept of al-tawahhud (productive solitude) understood in the philosophical framework of Ibn Bajjah, particularly in relation to the refinement of reason and inner happiness of humans? (2) In what aspects is Ibn Bajjah's concept of the solitary human being relevant to models of stress management and mental health in the perspective of modern psychology? (3) How can the limitations, therapeutic value, and potential application of the concept of al-mutawwa??id be adapted as a reflective strategy in dealing with the pressures of modern society? This study uses a qualitative method with a philosophical and comparative analysis approach. Primary sources are obtained from the work Tadb?r al-Mutawa??id, while secondary sources come from relevant academic literature in Islamic philosophy and modern psychology. The results of the study show that productive solitude according to Ibn Bajjah has therapeutic value that can strengthen emotional regulation, intellectual clarity, and moral integrity. This concept is not a form of social escape, but rather a reflective strategy that is in line with the mindfulness and self-regulation approaches in modern psychology. Thus, al-tawahhud can be a philosophical alternative to current mental health models.